Citzenship in deed : a study of the Action Project component in Civic, Social and Political Education (CSPE) in Ireland 2001-2013 - Wilson, Máirín (Trinity College (Dublin, Ireland). School of Education, 2015)
Civic, Social and Political Education (CSPE) is a mandatory subject within the Irish education system. Citizenship education forms part of the core curriculum in the three year Junior Cycle programme in Irish secondary schools. The syllabus requires students to do two Action Projects and to present one of these for assessment in the state examination in CSPE at the end of year three. This study examined the nature of those Action Projects.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin